2008
DOI: 10.1177/0192623307313011
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Air Pollution Exposure Is Associated with Neuroinflammation, an Altered Innate Immune Response, Disruption of the Blood-Brain Barrier, Ultrafine Particulate Deposition, and Accumulation of Amyloid β-42 and α-Synuclein in Children and Young Adults

Abstract: Air pollution is a serious environmental problem. We investigated whether residency in cities with high air pollution is associated with neuroinflammation/neurodegeneration in healthy children and young adults who died suddenly. We measured mRNA cyclooxygenase-2, interleukin-1beta, and CD14 in target brain regions from low (n = 12) or highly exposed residents (n = 35) aged 25.1 +/- 1.5 years. Upregulation of cyclooxygenase-2, interleukin-1beta, and CD14 in olfactory bulb, frontal cortex, substantia nigrae and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
655
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 789 publications
(683 citation statements)
references
References 94 publications
24
655
1
3
Order By: Relevance
“…This in turn is expected to profoundly impair cytoskeletal stability and axonal integrity and would facilitate the formation of NFTs and senile plaques in affected neurons, thereby tipping the balance from healthy to pathological aging and cognitive deterioration (Krstic and Knuesel, 2013). This view also strongly supports the hypothesis of a pivotal role of olfactory bulb-associated neuroinflammation (Calderon-Garciduenas et al, 2008, Majde, 2010 in the initiation of the late-onset AD.…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…This in turn is expected to profoundly impair cytoskeletal stability and axonal integrity and would facilitate the formation of NFTs and senile plaques in affected neurons, thereby tipping the balance from healthy to pathological aging and cognitive deterioration (Krstic and Knuesel, 2013). This view also strongly supports the hypothesis of a pivotal role of olfactory bulb-associated neuroinflammation (Calderon-Garciduenas et al, 2008, Majde, 2010 in the initiation of the late-onset AD.…”
Section: Introductionsupporting
confidence: 53%
“…During the course of aging, however, accumulating injuries to the olfactory system, e.g. by viruses (Majde, 2010) or pollution (Calderon-Garciduenas et al, 2008), may induce excessive neuroinflammation and ultimately lead to well described deterioration of the olfactory system (Lazarini et al, 2012). It is highly conceivable that this in turn will induce pathological changes in relayed brain centers (Koliatsos et al, 2004, Hu et al, 2012.…”
Section: Olfactory-limbic Pathways and Admentioning
confidence: 99%
“…It has been shown that chronic exposure to urban air pollution can lead to disruption of the blood-brain barrier, endothelial activation, and enhanced inflammatory status of the brain. 53 Second, high LDL levels have not been shown as an independent risk factor for IS in contrast to their high impact on cardiovascular outcomes. 54 However, the PMdriven acceleration of arterial plaque burden is maintained by LDL.…”
Section: Perspectives On Neurovascular Researchmentioning
confidence: 99%
“…Chronic exposure has shown to cause epithelium and respiratory alterations2 leading to other chronic health outcomes including nonfatal heart attacks,3 stroke,4 asthma,5, 6 and decreased lung function 7, 8. Fine particulate matter (PM 2.5 ) has also been associated with adverse neurological outcomes including cognitive delays in children,9, 10, 11 dementia and Alzheimers,12, 13, 14 and white matter abnormalities 14, 15, 16. Animal studies show that long‐term exposure to PM 2.5 can decrease total brain and white matter volumes 17…”
Section: Introductionmentioning
confidence: 99%